KAJIAN MUTU DAN NILAI TAMBAH PERBANDINGAN KEONG SAWAH DAN JAMUR TIRAM PUTIH PADA PEMPEK LENJER - Farado, Chairiel; Dasir, Dasir; Yani, Ade Vera (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2017)
Research on the topic "Quality Review and Analysis of the Added Value By Comparison Apple Snail (Pila ampullacea) and White Oyster Mushroom On Making Pempek Lenjer", using a randomized block design (RAK) which were arranged in a non factorial by comparison apple snail (Pila ampullacea) and white oyster mushroom factors which consists of five levels of treatment factor and repeated 4 (four) times. The parameters were observed in this study, chemical analysis includes the levels of protein and fiber content on pempek lenjer. Organoleptic test covering the aroma, taste and color with hedonic test and the level of elasticity with ranking test on pempek lenjer. While the analysis of the added value includes the added value on pempek lenjer from white oyster mushroom and apple snail. While organoleptic tests include aroma, taste and color with preference level test which conducted on pempek lenjer by comparison apple snail and white oyster mushroom. The highest protein content was found at S4 treatment (apple snail 100%: white oyster mushroom 0%) with an average value 14.02%. And the lowest protein content was found at S0 treatment (apple snail 0%: 100% white oyster mushroom) with an average value 5.98%. The highest fiber content was found at S0 treatment (apple snail 0%: 100% white oyster mushroom) with an average value 2.19% and lowest fiber content was found at S4 treatment (100% apple snail: white oyster mushroom 0%) with an average value 0.03%. The highest pleasure levels value of pempek lenjer aroma was found in S2 treatment (apple snail 50%: white oyster mushroom 50%) with an average value of 3.95 (rather preferred criteria). The highest pleasure levels value of pempek lenjer taste was found in S2 treatment (apple snail 50%: 50% of white oyster mushroom) with an average value 4.00 (preferred criteria). The highest pleasure levels value of the pempek lenjer colors was found in the treatment S1 (apple snail 0%: white oyster mushroom 100%) with an average value 4.30 (preferred criteria).